2012
DOI: 10.1016/j.landurbplan.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

More green space is linked to less stress in deprived communities: Evidence from salivary cortisol patterns

Abstract: a b s t r a c tGreen space has been associated with a wide range of health benefits, including stress reduction, but much pertinent evidence has relied on self-reported health indicators or experiments in artificially controlled environmental conditions. Little research has been reported using ecologically valid objective measures with participants in their everyday, residential settings. This paper describes the results of an exploratory study (n = 25) to establish whether salivary cortisol can act as a bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
556
4
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 888 publications
(605 citation statements)
references
References 62 publications
27
556
4
18
Order By: Relevance
“…An experimental study found that stress-induced cortisol in men can be reduced by viewing videos of street trees of varying density [20]. Other observational studies investigated depressed urban communities and found that higher densities of trees around residential neighborhoods were associated with heathier cortisol patterns, both in the saliva [21,22] and hair [19] of the residents; that is, people who live in neighborhoods with higher tree density levels have a more regular diurnal cortisol pattern [21] and collect less cortisol residue in their hair [19]. Some studies showed differences between men and women.…”
Section: Cortisol Patterns and Other Stress Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…An experimental study found that stress-induced cortisol in men can be reduced by viewing videos of street trees of varying density [20]. Other observational studies investigated depressed urban communities and found that higher densities of trees around residential neighborhoods were associated with heathier cortisol patterns, both in the saliva [21,22] and hair [19] of the residents; that is, people who live in neighborhoods with higher tree density levels have a more regular diurnal cortisol pattern [21] and collect less cortisol residue in their hair [19]. Some studies showed differences between men and women.…”
Section: Cortisol Patterns and Other Stress Indicatorsmentioning
confidence: 99%
“…Tree density is positively associated with lower crime rates [43,44,47,48,50], more optimal cortisol patterns [19][20][21]75], lower blood pressure [16,17], lower rates of obesity [62], lower allergy rates [27], higher cognitive development and performance [37,38], lower prescription rates of antidepression medication [40], and better pregnancy outcomes [23][24][25][26].…”
Section: Tree Densitymentioning
confidence: 99%
“…79 Green exposure has also been shown to prevent and mitigate stress, anxiety, and depression, [80][81][82][83] especially in urban environments. 81,84,85 Access to green views has been associated with improved mental health in general 86 and more specifically has been shown to reduce mental fatigue and improve coping with stressful settings. [87][88][89] Spending time in a garden or nature has been shown to be an effective therapy for stress-related mental health issues (i.e., nature-based rehabilitation).…”
Section: Urban Greening As Place-based Public Health Interventionmentioning
confidence: 99%
“…68,117 For instance, percent of green cover within a residential area is a common measure, 85,118 although this measure may not reflect actual exposure to green space. Adults tend to spend between 60 and 70 % of their time at home 119 and the rest of their time at a work or other locations.…”
Section: Refinement Of Measures Of Green Space Nature Health and Smentioning
confidence: 99%
“…A body of research suggests that having access to green space is associated with improved mental health and can have a greater impact on mental than physical health (Ohta et al, 2007;Sugiyama et al, 2008;Maas et al, 2009;Groenewegen et al, 2011). A number of mechanisms have been proposed to explain this association, including green space as a means for reducing stress and for increasing social cohesion and support (Sugiyama et al, 2008;Stigsdotter et al, 2010;van den Berg et al, 2010;Thompson et al, 2012), although whether it promotes physical exercise The impact of urban-rural environments on mental health 6 is less clear (see Groenewegen et al, 2011 for an overview).The relationship between type of living environment and health is, therefore, potentially multi-faceted.…”
Section: Introductionmentioning
confidence: 99%